The Effects of Instruction Dimension, Environmental Dimension and Student Trust Toward Indonesian Student’s Satisfaction in Online Learning of SAP (ERP) - Lita Kusumasari; Prima Rosita Arini; Jay Rajasakera; Badr Alsolami (Telaah Bisnis, 2021)
Student's satisfaction has important role in improving student's performance and the academic institution quality. Due to the outbreak of Covid-19, an academic institutes shifted their traditional learning methods to online classes. In teaching SAP, which is prominent software for Enterprise Resource Planning, the student's satisfaction requires further attention because of the subject complexity; in terms of delivery mode and infrastructure requirements. Hence, this paper aims at examining the student's satisfaction for SAP courses during the outbreak. The examination includes relationship between factors that include instructor's dimension, environmental dimension, student trust and student satisfaction. A total of 332 responses were collected from students who were involved in SAP subjects and experienced the transition of traditional teaching to online teaching of the subject. The data was analyzed using SPSS for descriptive analysis and AMOS for Structural Equation Modeling (SEM). Internal consistency of the research instrument, Kaiser-Meyer-Olkin measure of sampling adequacy and exploratory factor analysis revealed that the research instrument was suitable. The findings indicate that instruction dimension significantly affected environmental dimension, student trust and student satisfaction. Environmental dimension significantly affected student trust and student trust significantly affecting student satisfaction. Student trust is mediating the relationship between instruction dimension and environmental dimension toward student satisfaction. Moreover, the results show that instructor plays dominant role toward student trust and student satisfaction. The learning environment, which include interaction between students and lecturer, enhances the student to overcome difficulties while learning online. These findings are critical in understanding the students' satisfaction in online learning and contribute in improving the learning environment.